Visual narratives on organizational space. Issue 5 (5th August 2014) - Höykinpuro, Ritva; Ropo, Arja
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a visual perspective to the narrative management research by exploring the potential of drawings to construct organizational space. This study is explorative in nature and aims to open up a discussion on the importance of visuality within the narrative research. Visual narratives combined with written ones are constructed and analyzed in the paper. Design/methodology/approach – The empirical illustrations of visual narratives outline students' first-time encounters of the university campus. Their drawings and stories are used to describe and analyze their personal and subjective experiences of how they relate to the campus space. The students were asked to recall the moment they encountered the university campus for the first time and to draw their memories on a paper. Furthermore, they were asked to describe the drawings in a written narrative. Following that, the storyline was identified through a content analysis of both the drawings and the written narratives. This participatory research approach considers informants as co-researchers in producing data and emphasizes the inter-subjective nature of the study. Findings – The study points out valuable aspects in visual narrative organization research. The drawings and written narratives were found to complement each other revealing different things of the experiences. The drawings were very rich and detailed. They captured and revealed emotions, symbolic meanings and interpretations that were not explicated in the written stories. Finally, categories of visual narratives on organizational space were developed. Originality/value – This study contributes to the development of visual methodology in narrative management research. Moreover, this paper provides a methodological contribution to study organizational space. It sheds light on the potential of using visual narrative materials, especially self-produced drawings to construct organizational space. The study develops and illustrates a visual research method that combines written narratives with drawings. The study points out the importance to involve the informants as co-creators of a narrative study to capture the emotional richness of visual narratives. The authors envision that visual aspects of narratives will be a future direction in the narrative research, because visuality may capture hidden emotional aspects, symbols and artifacts that are not easily revealed in the told or written stories.